2011
DOI: 10.4238/vol10-2gmr1112
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of Aquilegia (Ranunculaceae) species and cultivars assessed by AFLPs

Abstract: ABSTRACT. Species of the genus Aquilegia are exceptionally diverse in their floral morphology and color, commonly known as columbine. They are widely planted ornamentals and are highly attractive for hummingbirds. However, little is known about their genetic diversity. We examined the genetic diversity of the species and cultivars using amplified fragment length polymorphism (AFLP) markers. Sixteen EcoRI/MseI AFLP primer combinations produced 327 informative polymorphic bands, with a mean of 20.4 bands scored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…The cluster analysis showed that cultivars from the same geographic regions tended to group together (Zhu et al, 2011). Cultivars from North America mainly grouped in Clusters A and B, while Chinese cultivars grouped in Cluster C. There was an interesting exception in that Nos.…”
Section: From 50mentioning
confidence: 92%
See 1 more Smart Citation
“…The cluster analysis showed that cultivars from the same geographic regions tended to group together (Zhu et al, 2011). Cultivars from North America mainly grouped in Clusters A and B, while Chinese cultivars grouped in Cluster C. There was an interesting exception in that Nos.…”
Section: From 50mentioning
confidence: 92%
“…DNA concentrations were estimated with Smart Ladder (TianGen) on a 1% (w/v) agarose gel containing Gel Red at 0.1 μg/mL 1X TAE buffer, with bands visualized under UV light (Zhu et al, 2011 …”
Section: Dna Extractionmentioning
confidence: 99%
“…DNA concentrations were estimated with Smart Ladder (TianGen) on a 1% (w/v) agarose gel containing Gel Red at 0.1 μg/ml in 1× TAE buffer, with bands visualized under UV light (Zhu et al. ).…”
Section: Methodsmentioning
confidence: 99%
“…DNA quality and concentration were measured by 1% agarose gel electrophoresis containing Gel Red at 0.1 mg/mL 1X TAE buffer, with bands visualized under UV light (Zhu et al, 2011).…”
Section: Dna Extractionmentioning
confidence: 99%